Alendronic acid‐induced oral mucosal ulceration: two case reports. (29th July 2020) - McLean, S.; Kelly, R.; Rajlawat, B.; Field, A.
Abstract: Alendronic acid is generally a well‐tolerated medication, however, there are well‐established adverse effects known within dentistry, such as medication‐related osteonecrosis of the jaw and upper gastro‐intestinal disturbances, particularly erosive oesophagitis. There is growing evidence of bisphosphonate‐induced oral ulcerations and this diagnosis needs to be considered for patients presenting with unexplained oral ulceration. An 84‐year‐old female patient with dementia presented at our emergency dental department with severe, painful oromucosal ulceration. Haematological investigation, including Indirect‐immunofluorescence demonstrated no abnormalities. Therefore, the likely diagnosis was that of chemically induced traumatic ulceration. The patient was managed through the cessation of alendronic acid, and the use of both topical and systemic corticosteroids. A 68‐year‐old female patient with learning difficulties presented with ulceration in the lower buccal sulcus following an urgent referral. The patients carer reported persistent difficulty in the swallowing of medicines, with medications regularly 'pouched' in the patients cheeks. Due to patient distress no further investigations were completed. Clinically, the lesion was characteristic of chemically induced traumatic ulceration. We therefore encouraged the continuation of liquid form alendronic acid. At a 2 week review, the ulceration had fully resolved. Alendronic acid‐induced ulceration should be considered for patients presenting with oral ulceration, particularly in those with cognitive impairments. There needs to be increased awareness of alendronic acid‐induced oral ulceration among prescribers, particularly in patients 'at risk'. Alternate preparations of this medication such as dispersible tablets and an oral solution are available.